Low population density settlement patterns on California's Northern Channel Islands - Jazwa, Christopher S.; Molter, Tyler R.; Morgan, Christopher T. (Frontiers in Environmental Archaeology, 2025)
Chronological and archaeofaunal data indicate that settlement of the earliest, low-density populations on California's Northern Channel Islands was conditioned by variables other than those affecting later, high-density populations. We use a variant of the Ideal Free Distribution (IFD) with considerations for low population densities to model early settlement on Santa Rosa Island (SRI). Early in time, individuals could have maximized their per-capita resource return at the mouth of any of SRI's 19 major drainages, so it was not necessary to distribute themselves in only those habitats with the highest potential return rate. Instead, while some individuals targeted high-ranked habitats, others settled at low-ranked habitats along the south coast that traditional IFD model variants predict would be first settled later. These habitats may have been targeted for other, less often considered environmental characteristics that might have been less important during periods characterized by higher population density or resource stress, perhaps including protection from prevailing northwesterly storms. During the relatively dry Middle Holocene, when population density increased and there was a greater focus on the high-ranked northwest coast, settlement intensity on the south coast did not increase and may have decreased. Later, as settlement at high-ranked habitats in-filled to the point that traditional IFD models predict the lowest-ranked habitats should be settled, there is evidence of population growth and reoccupation on the south coast. This study has implications for understanding initial colonization of new geographic areas, including larger regions in which the settlers did not have complete knowledge of all potential settlement locations.